2021
DOI: 10.3390/ijerph18031135
|View full text |Cite
|
Sign up to set email alerts
|

LACE Score-Based Risk Management Tool for Long-Term Home Care Patients: A Proof-of-Concept Study in Taiwan

Abstract: Background: Effectively predicting and reducing readmission in long-term home care (LTHC) is challenging. We proposed, validated, and evaluated a risk management tool that stratifies LTHC patients by LACE predictive score for readmission risk, which can further help home care providers intervene with individualized preventive plans. Method: A before-and-after study was conducted by a LTHC unit in Taiwan. Patients with acute hospitalization within 30 days after discharge in the unit were enrolled as two cohorts… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 48 publications
0
5
0
Order By: Relevance
“…46 Another study suggested that a data-driven approach for scheduling post-discharge interventions leads to a significant reduction in readmission rate by 44.7%, compared to regular visit-based home care. 47 With the accurate risk stratification in addition to the time-to-readmission outcome prediction, it is more likely to identify the most vulnerable period of each patient, such as the segment of the time-to-readmission risk curve where the slope changes drastically or when the risk exceeds a pre-set threshold. Thus, the scheduling of follow-up can be better tailored and individualized, and timeliness could be ensured.…”
Section: Discussionmentioning
confidence: 99%
“…46 Another study suggested that a data-driven approach for scheduling post-discharge interventions leads to a significant reduction in readmission rate by 44.7%, compared to regular visit-based home care. 47 With the accurate risk stratification in addition to the time-to-readmission outcome prediction, it is more likely to identify the most vulnerable period of each patient, such as the segment of the time-to-readmission risk curve where the slope changes drastically or when the risk exceeds a pre-set threshold. Thus, the scheduling of follow-up can be better tailored and individualized, and timeliness could be ensured.…”
Section: Discussionmentioning
confidence: 99%
“…In 2017, only 5.8% of all long-term care patients used institutional care, while 94.2% received home-based care [ 5 ]. Home care patients often have multiple comorbidities, which is demonstrated by the fact that 90.04% are classified into resource utilization groups 2 and 3 [ 6 , 7 ]. These patients require one or two additional specialized care services over and above ordinary healthcare services provided to group 1-classified patients.…”
Section: Introductionmentioning
confidence: 99%
“…Most European countries consider home care as a priority in their health system. 17,18 The World Health Organization also prioritizes prevention and home care programs and emphasizes early discharge and continued home care. However, the health system in Iran has a treatment-based approach in which hospital care is preferable to community-based care in the health system.…”
Section: Discussionmentioning
confidence: 99%